Kristenisasi dan Perkembangan Gereja Protestan Gementee Malang pada Awal Abad Ke-20 - Wijaya, Daya Negri; Mufti, Muhammad 'Afwan; Dhani, Arif Perwira; Rahmah, Nadya; Hartono (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2026)
This study aims to examine the process of Christianization in the Malang residency in the 20th century, which is related to Dutch colonial practices. This study uses a historical method, this study has several stages, namely heuristics, criticism, interpretation, and historiography. The results of this study indicate that Christianization in Malang cannot be separated from the long history of the arrival of Catholics with Portuguese traders in Maluku in 1511 and the spread of Christianity (Protestantism) through the activities of the VOC in the 19th century. This study focuses on the development of Christianity in Malang which was influenced by European migration, infrastructure development, and socio-political changes during the colonial period. Through cultural and educational acculturation carried out by the Dutch colonial government became the main strategy in the spread of this religion. The Immanuel Protestant Church of West Indonesia (GPIB) Malang, which was founded in 1861, is an important symbol of Christianization in Malang and until now functions as a service center for Christian congregations. This study concludes that the colonial government and missionary institutions worked together to integrate Christianity into the social and educational structures in Malang, which not only increased the Christian population but also formed a sustainable religious community through the establishment of churches, especially Immanuel Church, as one of the symbols of this change. Keywords: Christianization, Church, Dutch Colonialism and Malang.